Design of an Audio Compressor with Digital Control - Montenegro, Jonnathan (TECCIENCIA, 2021)
Based on the concepts and insights of cybernetic theory and the applications of applied electronic engineering and control, this article deals with the design of an analog compressor with digital control. The main purpose of the device is to control the basic parameters of a hardware using an application on a micro-controller. The advantage of that design is the possibility of store the different analog positions into a digital position of the memory of the micro-controller, in order to call these presets whenever its needed. Further possible applications include the virtual-remote monitoring of events where the interaction between artist and sound engineering is required.